Vascular Accesses for Haemodialysis in the Upper Arm Cause Greater Reduction in the Carotid-Brachial Stiffness than Those in the Forearm: Study of Gender Differences - Bia, Daniel (2012)
Purpose. To evaluate in chronically haemodialysed patients (CHPs), if: (1) the vascular access (VA) position (upper arm or forearm) is associated with differential changes in upper limb arterial stiffness; (2) differences in arterial stiffness exist between genders associated with the VA; (3) the vascular substitute (VS) of choice, in biomechanical terms, depends on the previous VA location and CHP gender. Methods. 38 CHPs (18 males; VA in upper arm: 18) were studied. Left and right carotid-brachial pulse wave velocity (PWVc-b) was measured. In in vitro studies, PWV was obtained in ePTFE prostheses and in several arterial and venous homografts obtained from donors. The biomechanical mismatch (BM) between CHP native vessel (NV) and VS was calculated. Results/Conclusions. PWVc-b in upper limbs with VA was lower than in the intact contralateral limbs (P < 0.05), and differences were higher (P < 0.05) when the VA was performed in the upper arm. Differences between PWVc-b in upper limbs with VA (in the upper arm) with respect to intact upper limbs were higher (P < 0.05) in males. Independently of the region in which the VA was performed, the homograft that ensured the minimal BM was the brachial artery. The BM was highly dependent on gender and the location in the upper limb in which the VA was performed.